Antenatal Risk Factors of Children with Cerebral Palsy: An Experience of Center for the Rehabilitation of the Paralysed (CRP) in Bangladesh - Hossain, Md Anwar; Sharmin, Saida; Afrin, Atia; Shahrin, Tunazzina; Hossain, Mahabub (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Cerebral palsy (CP) in children is an important global public health issue in terms of its outcome, quality of life, and life expectancy. Objective: To identify the types of cerebral palsy and the antenatal risk factors related to cerebral palsy in children attending a tertiary level specialized rehabilitation institution in Bangladesh. Methods: This cross-sectional, descriptive study was conducted, between September 2021 and January 2022, among 72 parents/caregivers of children with cerebral palsy at Center for Rehabilitation for Paralyzed (CRP), Dhaka, Bangladesh. Data were collected through face-to-face interview through semi-structured questionnaire. The mean and standard deviation were used to examine quantitative variables, whereas percentages were used to summarize qualitative variables. Results: The most common age group of children was of this study 3-5 years (59.7%). Female predominance (54%) was observed. Most of the respondents (61.1%) came from the joint family.At the time of childbirth, most (81.9%) of the respondents were in the 20-35 years age group. History of consanguinity was found in 19.4% cases. Among categories of the cerebral palsy, spastic type was the most prevalent (40.3%), followed by dyskinetic type (31.9%), mixed type (23.6%), and hypotonic type (4.2%). Among antenatal factors, maternal infection (13.9%), trauma during pregnancy (12.5%), maternal diabetes (13.9%) and hypothyroidism (11.1%), antepartum hemorrhage (12.5%), congenital brain malformation (4.2%) and maternal epilepsy (1.4%) were found as risk factors of cerebral palsy in children. Conclusion: Our study revealed that spastic type of cerebral palsy was the dominant form of the disease in children. The most affected age group of children was 3-5 years. Surprisingly, a female predominance was observed. Maternal infection (13.9%), diabetes (13.9%), and ante-partum hemorrhage (12.5%) were among the most common antenatal factors. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 35-39